The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/1469-0691.12290
|View full text |Cite
|
Sign up to set email alerts
|

Transportation capacity for patients with highly infectious diseases in Europe: a survey in 16 nations

Abstract: Highly infectious diseases (HIDs) are defined as being transmissible from person to person, causing life-threatening illnesses and presenting a serious public health hazard. In most European Union member states specialized isolation facilities are responsible for the management of such cases. Ground ambulances are often affiliated with those facilities because rapid relocation of patients is most desirable. To date, no pooled data on the accessibility, technical specifications and operational procedures for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…The prevalence of PVL gene in different regions is diverse. In Europe, Glasner et al (2015) tested 147 spa 437-MRSA strains in 11 European countries for PVL gene, and the positive rate was as high as 82%. In Asia, the prevalence of PVL in CA-MRSA and HA-MRSA was 14.3 and 5.7%, respectively ( Song et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PVL gene in different regions is diverse. In Europe, Glasner et al (2015) tested 147 spa 437-MRSA strains in 11 European countries for PVL gene, and the positive rate was as high as 82%. In Asia, the prevalence of PVL in CA-MRSA and HA-MRSA was 14.3 and 5.7%, respectively ( Song et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant STs (ST188, ST59 and ST6) in this study were consistent with other community-based populations [ 31 33 ], but some other STs were also previously reported in hospital patients (ST338 and ST1) [ 34 36 ] and animals (ST398 and ST1) [ 37 39 ], which might indicate the cross transmission of isolates in different sources. CC59, the most predominant clonal complex types of MRSA in our study, is the predominant community-associated MRSA clone in Asia [ 40 ]. CC5, the third major CC types of MRSA in this study, was reported to be the main CC type of HA-MRSA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…ESBL-producing E. coli belonging to CC ST131-phylogroup B2 are usually associated with more virulent strains ( Overdevest et al, 2015 ). These were frequently found in the Dutch hospitals included in the present study but only sporadically in the community samples.…”
Section: Discussionmentioning
confidence: 99%